Hegel's Discovery of the Philosophy of Spirit - Ifergan, P. author. aut Link
X, 253 p.
Keywords: This exploration of Hegel's critique of the individualistic ethos of modernity and the genesis of his alternative vision traces the conceptual schemes Hegel experimented with to show how he settled on the concepts of 'ethical life' (Sittlichkeit) and Spirit as the means for overcoming subjectivity and domination.